Drie geslagte Du Toit-Bybelvertalers - V. E. d'Assonville (Acta Theologica)
Bible translation has a long history on the continent of Africa, in particular if one considers the Septuagint. In the 19th and 20th centuries in South Africa, three prominent translators of the Bible into Afrikaans, the three generations of the Du Toit family, namely S.J. du Toit (the grandfather, 1847-1911), J.D. du Toit (the father, 1875-1953) and S. du Toit (the son, 1905-1982), have applied a Bible translation principle that dates back more than 15 centuries to Augustine of Northern Africa. This article outlines the work as well as the principles used by these three generations in translating the Bible from the original languages, Hebrew and Greek.